Crust-Magma Interactions of the Hengill Volcanic Complex in Iceland - Gress, Nathan (The Ohio State University, 2013)
This research has determined the relationship between magma evolution and pressures of partial crystallization at the Hengill volcanic complex in Iceland. Petrologic studies determined pressure, therefore depth, of partial crystallization to complement seismic studies which have difficulty providing details of crustal structure at depths greater than 9km due to resolution. This research has explored implications of petrologic results to provide information about the magma plumbing system beneath Hengill. Hengill is located in SW Iceland in the western rift zone and is the site of a mid ocean ridge intersecting with a transform margin marked by the South Iceland Seismic Zone. Previous work by Tronnes, and by Gurenko and Sobolev, provide analyses of basaltic glasses representing quenched magmas. Tronnes divided the analyses into 4 groups, based on chemical composition and occurrence of various clinopyroxene phenocrysts and xenocrysts. Two of the groups contain clinopyroxene xenocrysts that show clear evidence for resorbtion. Gurenko and Sobolev’s study involved glass samples in gabbroic xenoliths with resorbed clinopyroxene at the contact between the xenocryts and magma. Variations in chemical composition shown by these analyses were used to study the evolution of Hengill’s magmas and to calculate pressures of partial crystallization. Nearly all available glass analyses were used in this study. A small number of samples were filtered out of the data set because they have anomalously high silica contents, anomalous aluminum contents, or anomalous concentrations of other elements (see Kelly and Barton, 2008, for discussion). Plots of oxide concentrations versus MgO indicate samples that contain the resorbed clinopyroxenes do not follow the same trends as the other glass samples. The latter samples are the results of the processes of crystallization and, therefore, the different trends show the effects of crust and magma interacting with each other (clinopyroxene assimilation) in the samples containing resorbed clinopyroxene. Calculated pressures of partial crystallization are used to infer a magma chamber depth of approximately 15km. This is slightly deeper but similar to that of Kelley and Barton’s calculation of 12km and Gurenko and Sobolev’s 10km. Interpretation of these calculations is not straightforward. Resorbed clinopyroxenes and evidence for crustal contamination may lead to anomalous results and skew the pressure data if not taken into account, appearing to generate pressures that can be far lower than the actual conditions that caused their compositions at the time of crystallization. No embargo